Linking biological and geological data on dinoflagellates using the genus Spiniferites as an example: the implications of species concepts, taxonomy and dual nomenclature. (20th December 2018) - Ellegaard, Marianne; Head, Martin J.; Versteegh, Gerard J.M.
Abstract: Dinoflagellates encompass two taxonomic systems (dual taxonomy) reflected by separate traditions of nomenclature: one based mainly on living motile stages, and the other mainly on fossil cysts (dual nomenclature). Modern cysts may therefore bear two names if their life cycle is known. There have been attempts to rationalize this duality, but at species and genus level this has been largely unfruitful. New and continuing developments call for a renewed evaluation of this duality: (1) the elucidation of multiple new cyst–motile stage relationships creating overlaps between cyst-based and motile-based systems, and (2) the advent of DNA sequence-based phylogenies, revealing evolutionary patterns (underlying the phenotypic differences) that disagree with trees obtained from the study of fossil cysts. We examine the background of dual nomenclature and discuss the implications of new advances in molecular phylogeny for dual taxonomy as well as briefly review earlier attempts to unite cyst/fossil and motile-/living-based nomenclatures. From this basis, we explore routes for bringing the separate taxonomic systems closer together. Our rationale for doing this lies in the challenges facing communication between the biologists and geologists who work on these different life cycle stages. These challenges encompass taxonomic issues, nomenclature, evolutionary interpretations, and the nature of what we perceive as a species. We use the motile/cyst pair Gonyaulax / Spiniferites as our example, as these, and related genera, provide a useful model for illustrating the difficulties in bridging the gap between biology and palaeontology because they are numerous, with regard to both species and specimens, and are ubiquitous in both time and space.